PENGEMBANGAN APLIKASI PENGENALAN GEDUNG UNIVERSITAS PENDIDIKAN GANESHA BERBASIS MARKERLESS AUGMENTED REALITY - Dewa Ayu Putu Putri Sanjani; Padma Nyoman Crisnapati; I Made Agus Wirawan; I Gede Mahendra Darmawiguna (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2015)
An organisation and institution need a technology to convey any information. As an institution of education, UNDIKSHA has used website as a media of information. However the information about buildings of UNDIKSHA still incomplete. Because of that, common people get confused to find specific location in UNDIKSHA. They should ask students they met to find the location. The objective of this research is to design and implement an application which will be used as a media to introduce the building of UNDIKSHA to the public. The research method used in this research was research and development. The application of the Introduction of UNDIKSHA’s building which used Markerless Augmented Reality Based was developed with waterfall model. This application which used Java Programming Language was implemented with Eclipse as its editor and ADT plug-ins and Metaio as an additional detection library because it is capable in detecting based on GPS. This application used AndEngine as a library for designing. The main function of this application is to detect any building of UNDIKSHA, it will display the information of building’s name and the detail information of building which has been detected. The buildings which will be detected is in Kampus Tengah and Kampus Bawah of UNDIKSHA. Based on the result of the test, this application can be worked on Android devices that have been tested with different specification. All of the features in this application can be worked on all of devices. The result of sound quality and music were good.